Decolorization of an azo dye Orange G in aqueous solution by Fenton oxidation process: Effect of system parameters and kinetic study - Sun, Sheng-Peng; Li, Cheng-Jie; Sun, Jian-Hui; Shi, Shao-Hui; Fan, Mao-Hong; Zhou, Qi (Journal of hazardous materials, 2009)
To establish cost-efficient operating conditions for potential application of Fenton oxidation process to treat wastewater containing an azo dye Orange G (OG), some important operating parameters such as pH value of solutions, dosages of H 2O 2 and Fe 2+, temperature, presence/absence of chloride ion and concentration of the dye, which effect on the decolorization of OG in aqueous solution by Fenton oxidation have been investigated systematically. In addition, the decolorization kinetics of OG was also elucidated based on the experimental data. The results showed that a suitable decolorization condition was selected as initial pH 4.0, H 2O 2 dosage 1.0 × 10 −2 M and molar ratio of [H 2O 2]/[Fe 2+] 286:1. The decolorization of OG enhanced with the increasing of reaction temperature but decreased as a presence of chloride ion. On the given conditions, for 2.21 × 10 −5 to 1.11 × 10 −4 M of OG, the decolorization efficiencies within 60 min were more than 94.6%. The decolorization kinetics of OG by Fenton oxidation process followed the second-order reaction kinetics, and the apparent activation energy E, was detected to be 34.84 kJ mol −1. The results can provide fundamental knowledge for the treatment of wastewater containing OG and/or other azo dyes by Fenton oxidation process.